2022
DOI: 10.1101/2022.06.12.22276048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of COVID-19 and Long COVID in Collegiate Student Athletes from Spring 2020 to Fall 2021: A Retrospective Survey

Abstract: Symptomatic COVID-19 and post-COVID conditions, also referred to as post-acute sequelae of SARS-CoV-2 (PASC) or Long COVID, have been widely reported in young, healthy people, but their prevalence has not yet been determined in student athletes. We surveyed a convenience sample of 18 collegiate school administrators, representing about 7,000 student athletes. According to their survey responses, 9.8% of student athletes tested positive for COVID-19 in spring 2020 and 25.4% tested positive in the academic year … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Furthermore, athletes with a higher estimated predVO 2 are less likely to suffer from persistent symptoms. This is consistent with the findings by Massey et al [32] who also found a lower prevalence of Long-Covid in athletes compared with the general population.…”
Section: Prediction Of Peak Oxygen Consumption Before Infectionsupporting
confidence: 93%
“…Furthermore, athletes with a higher estimated predVO 2 are less likely to suffer from persistent symptoms. This is consistent with the findings by Massey et al [32] who also found a lower prevalence of Long-Covid in athletes compared with the general population.…”
Section: Prediction Of Peak Oxygen Consumption Before Infectionsupporting
confidence: 93%